The effect of probiotic-fortified kefir on depression, appetite, oxidative stress, and inflammatory parameters in Iranian overweight and obese elderly: a randomized, double-blind, placebo-controlled clinical trial - Mehran Noori; Zainab Shateri; Siavash Babajafari; Mohammad Hadi Eskandari; Karim Parastouei; Mohammad Ghasemi; Hoseein Afshari; Mohammad Samadi (Journal of Health, Population and Nutrition)
Abstract Background It has been shown that the microflora of the gastrointestinal tract undergoes changes in obese individuals. The present study aimed to investigate the effect of kefir fortified with two strains, Lactobacillus helveticus and Bifidobacterium longum, on depression, appetite, oxidative stress, and inflammatory parameters in overweight and obese elderly individuals. Methods This study was a double-blind, randomized, and placebo-controlled clinical trial conducted on 67 elderly men aged over 65, who were randomly divided into two groups. One group (n = 35) received one bottle (240 cc) of regular kefir as a placebo, while the intervention group (n = 32) received one bottle of probiotic-fortified kefir for eight weeks. Depression and appetite were evaluated using the Geriatric Depression Scale-15 (GDS-15) and a validated Visual Analogue Scale (VAS), respectively. Oxidative stress parameters were assessed using the standard calorimetric method, and inflammatory parameters were measured via the enzyme-linked immunosorbent assay method (ELISA). The differences between the two groups were compared using the independent samples T-test. Results The median age of participant in both groups was 65 years. A significant difference in depression scores and the mean change between the two groups was observed after eight weeks (p = 0.001 and p = 0.042, respectively). Within-group comparison revealed a significant increase in appetite scores in both groups (p < 0.05 for both). Moreover, a significant difference in the changes in total antioxidant capacity (TAC) was noted (p = 0.009). However, no significant differences were observed in other oxidative and inflammatory parameters between the two groups (p˃0.05 for all). Conclusions The results demonstrated the positive impact of two specific strains of Bifidobacterium and Lactobacillus on improving depression in the elderly. However, when comparing the two groups, no significant effects were observed on appetite, inflammation, and oxidative stress parameters, except for TAC.